A metal–organic framework as a "turn on" fluorescent sensor for aluminum ions. Issue 2 (8th December 2016) - Yu, Mei-Hui; Hu, Tong-Liang; Bu, Xian-He
Abstract : A new three-dimensional (3D) metal–organic framework exhibits high sensitivity and selectivity for Al 3+ ions as a "turn on" fluorescent sensor. Abstract : Aluminum ions are harmful to human health and can damage the central nervous system leading to brain cell injury in excessive amounts. Hence, sensing and detection of Al 3+ ions are important and require a method with high sensitivity and high selectivity. Here, a metal–organic framework [Zn2 (O-BTC)(4, 4′-BPY)0.5 (H2 O)3 ]·(H2 O)1.5 ·(DMA)0.5 n (NUM-2 ) was constructed by ligands 2-hydroxy-benzene-l, 3, 5-tricarboxylic acid (HO-H3 BTC) and 4, 4′-bipyridine (4, 4′-BPY) based upon chain-shaped secondary building units (SBUs).NUM-2 itself exhibits extremely weak fluorescence emission, however, the luminescence intensity ofNUM-2 is enhanced obviously when there are Al 3+ ions in ethanol solutions, and the detection limit calculated using 3 σ / k could reach 0.10 ppm, indicating thatNUM-2 could be used as an efficient turn-on-based fluorescent sensor with high sensitivity and high selectivity for Al 3+ ions.